Kuantitas dan kualitas telur ayam arab (Gallus turcicus) silver dan gold - M. H. Yumna; Achmanu Zakaria; V. M. Ani Nurgiartiningsih (Faculty of Animal Science, Universitas Brawijaya, 2013)
This research was conducted to examine egg quantity and quality of Silver and Gold Arabic chicken (Gallus turcicus). The materials used in this study were 30 Silver and 30 Gold Arabic chicken aged 8-9 months which had mean of initial body weight were 1,93±0,13 and 2,00±0,15 kg respectively. The method was experiment on two groups of Arabic chicken based on feather color (Silver and Gold). Data was analyzed by unpaired t test. The study shows that egg weight of Gold Arabic chicken (46.81±2.41 g) was significantly heavier (P<0.01) than that of Silver Arabic chicken (42.75±2.22 g). However, there were no significant difference on egg number, egg index, yolk color eggs, yolk protein content, yolk fat content, and Haugh units among these two chickens. It could be concluded that Gold Arabic chicken could produce heavier egg weight than the Silver one although there were no differences on egg number, egg index, yolk color eggs, yolk protein content, yolk fat content, and Haugh units. The study suggests breeding Gold Arabic chickens due to its egg weight production. Keywords: Arabic chicken, feather color, quantity and quality eggs